1997
DOI: 10.1016/s0014-5793(97)00718-7
|View full text |Cite
|
Sign up to set email alerts
|

Dioxygenation of N‐linoleoyl amides by soybean lipoxygenase‐1

Abstract: Anandamide, a novel neurotransmitter, has been reported to be dioxygenated by brain lipoxygenase [1, 11]. Anandamides constitute a new class of neuroregulatory fatty acid amides. However, little is known about the enzymatic dioxygenation of these lipids. Therefore, we have tested several members of the neuroactive fatty acid amide class containing a 1Z,4Z‐pentadiene system whether they could be dioxygenated by soybean lipoxygenase‐1, which is a model enzyme for mammalian lipoxygenases. In this study it was fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…The HAEAs were isolated with SPE (Bakerbond, 500 mg), analyzed, and purified by reversed phase and chiral phase high-performance liquid chromatography (HPLC) as reported. 44,45,48 12 (q, 1H), 3.72 (t, 2H) 3.42 (q, 2H), 2.97 (m, 2H), 2,82 (m, 2H), 2.22 (t, J ) 7.5 Hz, 2H), 2.11 (m, 2H), 1.72 (q, J ) 40, February 18, 1992) and were approved by the Animal Care Committee (University of Rome "Tor Vergata"). Rat forebrain and spleen membrane preparations were obtained using the method of Devane et al 49 and were stored at a concentration of 1 mg mL -1 protein in 50 mM Tris‚HCl, 2 mM Tris‚EDTA, 3 mM MgCl2 buffer, pH 7.4, at -80°C for no longer than 1 week.…”
Section: Methodsmentioning
confidence: 99%
“…The HAEAs were isolated with SPE (Bakerbond, 500 mg), analyzed, and purified by reversed phase and chiral phase high-performance liquid chromatography (HPLC) as reported. 44,45,48 12 (q, 1H), 3.72 (t, 2H) 3.42 (q, 2H), 2.97 (m, 2H), 2,82 (m, 2H), 2.22 (t, J ) 7.5 Hz, 2H), 2.11 (m, 2H), 1.72 (q, J ) 40, February 18, 1992) and were approved by the Animal Care Committee (University of Rome "Tor Vergata"). Rat forebrain and spleen membrane preparations were obtained using the method of Devane et al 49 and were stored at a concentration of 1 mg mL -1 protein in 50 mM Tris‚HCl, 2 mM Tris‚EDTA, 3 mM MgCl2 buffer, pH 7.4, at -80°C for no longer than 1 week.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have shown that NAE 18:2 and NAE 18:3 could be converted into hydroperoxy NAE by purified soybean (Glycine max) lipoxygenase-1 (LOX; Van der Stelt et al, 1997, 2000. The hydroperoxides of NAE 18:2 and NAE 18:3 could subsequently be converted by alfalfa (Medicago sativa) hydroperoxide (HPO) lyase and flax (Linum usitatissimum) seed allene oxide synthase (AOS) into novel oxylipins (Van der Stelt et al, 2000).…”
mentioning
confidence: 99%
“…(22). Linoleoylethanolamide ((9Z,12Z)-octadeca-9,12-dienoylethanolamide; ODNHEtOH), linoleoylamide ((9Z,12Z)-octadeca-9,12-dienoylamide; ODNH 2 ), linoleoylmethylamide ((9Z,12Z)-octadeca-9,12-dienoylmethylamide; ODNHMe), and their 13-hydroxy derivatives (13-HODNHEtOH, 13-HODNH 2 , and 13-HODNHMe) were synthesized and characterized (purity Ͼ96% by gas-liquid chromatography) as reported (23). 15-Hydro(pero)xyanandamide (15-hydro(pero)xyeicosa-(5Z,8Z,11Z,13E)-tetraenoylethanolamide; 15-H(P)AnNH; purity Ͼ96%) and 11-hydro(pero)xyanandamide (11-H(P)AnNH; a mixture of 45% 11-H(P)AnNH, 24% 5-H(P)AnNH, 18% 15-H(P)AnNH, 9% 8/9-H(P)AnNH, and 4% 12-H(P)AnNH by reversed-phase high performance liquid chromatography) were a gift from Guus van Zadelhof (Bijvoet Center for Biomolecular Research, Utrecht University).…”
mentioning
confidence: 99%